THE EFFECTIVENESS OF TAHFIDZ MANAGEMENT AT PESANTREN AL-HUSAINY BIMA - Anam, Khairul; Nurhasanah, Zakia; Al-Maulidi, Asrorul Fuad (STKIP Pesisir Selatan, 2025)
This study explores various aspects of Qur’anic memorization (tahfidz) management, including planning, organization, implementation, control, and other influencing factors. This research employs a qualitative case study approach, utilizing data collection techniques such as observation, interviews, and documentation. The research design follows a qualitative descriptive method, as the researcher aims to uncover facts and interpret the management of Qur’anic memorization at Al-Husainy Islamic Boarding School in Bima. The data were analyzed using the Miles and Huberman analysis model. The results of the study show that the Qur’anic memorization management implemented by Al-Husainy Boarding School in Bima has a social impact on the students within the pesantren environment. The students are motivated to take part in the tahfidz program, as it serves as an upgrading initiative for them. From a management perspective, this program enhances the quality of Qur’anic education for students by addressing common challenges such as poor recitation, unmet memorization targets, inconsistent memorization methods, and the selection of Qur’anic manuscripts. This study holds significant relevance in the context of Islamic education, as Qur’anic memorization is one of the core pillars of religious learning in Islam.